2021
DOI: 10.1038/s41398-021-01681-4
|View full text |Cite
|
Sign up to set email alerts
|

A human iPSC-astroglia neurodevelopmental model reveals divergent transcriptomic patterns in schizophrenia

Abstract: While neurodevelopmental abnormalities have been associated with schizophrenia (SCZ), the role of astroglia in disease pathophysiology remains poorly understood. In the present study, we used a human induced pluripotent stem cell (iPSC)-derived astrocyte model to investigate the temporal patterns of astroglia differentiation during developmental stages critical for SCZ using RNA sequencing. The model generated astrocyte-specific gene expression patterns during differentiation that corresponded well to astrogli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…Many studies have not actually investigated the status of astroglial cells during postnatal brain development, but were limited to the postmortem examination of adult brain tissues where dysregulation evident in developing astroglial cells are hidden, whereas this may have profound effects on the formation and maturation of neuronal networks. In line with this hypothesis, recent studies of in vitro cultures of human glial progenitors taken from SCZ patients has shown that the genes associated with glial differentiation in particular those associated with early oligodendroglial and astroglial lineage progression and those encoding for glia-derived metalloproteinases, were disrupted, thus indicating the existence of a cell autonomous glial pathology (Szabo et al, 2021;Windrem et al, 2017).…”
Section: Evidences For Astrocytes Alterations In Schizophreniamentioning
confidence: 83%
“…Many studies have not actually investigated the status of astroglial cells during postnatal brain development, but were limited to the postmortem examination of adult brain tissues where dysregulation evident in developing astroglial cells are hidden, whereas this may have profound effects on the formation and maturation of neuronal networks. In line with this hypothesis, recent studies of in vitro cultures of human glial progenitors taken from SCZ patients has shown that the genes associated with glial differentiation in particular those associated with early oligodendroglial and astroglial lineage progression and those encoding for glia-derived metalloproteinases, were disrupted, thus indicating the existence of a cell autonomous glial pathology (Szabo et al, 2021;Windrem et al, 2017).…”
Section: Evidences For Astrocytes Alterations In Schizophreniamentioning
confidence: 83%
“…Nevertheless, our study suggests that such differences may well occur at least in the subset of SCZ patients. Importantly, abnormalities in ECM have been among the strongest findings in iPSC‐derived brain cells already in three datasets (Kathuria et al, 2019 ; Szabo et al, 2021 ; Tiihonen et al, 2021 ), highlighting its importance in the pathophysiological process of SCZ. The reproducible results suggest the intriguing possibility that SCZ may be primarily a disease of ECM of the brain: abnormal and insufficient cell adhesion and ECM may result into abnormal neuron guidance and synaptogenesis, leading to imbalance in GABA/glutamate balance, and, finally, to clinical symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesize that glutamate metabolism is altered in SCZ cultures and could be the source of the phenotype seen in the current study. In accordance, SCZ iPSC-derived astrocytes have been shown to decrease glutamate uptake (30). Further research will have to con rm a potential causal role for GC2 in the altered glutamate clearance currently seen in SCZ and potentially even in the synaptic imbalance of the disorder.…”
Section: Discussionmentioning
confidence: 91%
“…Astrocytes were derived from the iPSCs according to our previously published protocol (30,(40)(41)(42) Neuronal differentiation…”
Section: Ipsc Generation and Astrocytes Differentiationmentioning
confidence: 99%
See 1 more Smart Citation